Comprehensive Analysis of the State of Technology in the Field of Waste Heat Recovery from Grey Water - Beata Piotrowska; Daniel Słyś (Energies, 2022)
The use of energy from waste can be a key means of reducing the consumption of fossil fuels and thus reduction of greenhouse gas emissions. Waste energy can be a worthy alternative to conventional energy sources in construction. This paper presents data on energy consumption for the preparation of domestic hot water in residential buildings. A review of the literature sources and inventions in the area of waste energy recovery from grey water was carried out. It also presents the results of research on prototypes of devices used to receive energy deposited in wastewater, published in recent years. The benefits of using drain water heat recovery systems for preheating utility water in residential buildings are presented. An analysis of technical solutions for grey water energy collection units was made, revealing their advantages and disadvantages. Great importance was attached to the review of patent sources as well as devices available on the market. According to the authors, the results of the technical review may be useful for contractors and designers of heat recovery equipment and installations, researchers and potential users of these technologies.